CFD analyses and design of a turbocompound system - Vogel, Thomas; Epple, Philipp; Hermann, Andreas; Grashof, Bettina; Delgado, Antonio (ASME International Mechanical Engineering Congress and Exposition, Proceedings (IMECE), 2013)
In a turbocompound (TC) system a turbocharged engine is coupled with an additional power turbine, which recovers exergy of the exhaust gas after the turbocharger. The gained power is added to the engine power by a gearbox and a hydrodynamic coupling. The benefit of turbocompound is that the efficiency of internal combustion engines is improved substantially.The challenge with turbocompounding is that a high speed turbine is coupled with a slow speed engine. Through the transient requirements in mobile applications the operating points of the engine are variable while the turbo machine is designed for a continuous and steady flow. Matching the components is an additional challenge in designing the flow path of a TC System. A systematic approach in which the flow path is divided into three regions is applied: the interstage duct, the power turbine consisting of the rotor and its guide vane as well as the exhaust gas collector. After defining performance criteria for the individual regions, they are analysed by computational fluid dynamics (CFD). For this purpose, the model for the CFD-simulation is validated with measurements. For the interstage duct the influence of the mass flow and the outlet swirl of the turbocharger are analysed. For the exhaust gas collector the influence of the outlet swirl and mass flow from the power turbine is evaluated by a sensitivity study. Based on verified CFD simulations as well as analytical considerations it was possible to show that an improvement of the turbine performance is still possible. Parameters to be optimized were identified. As a result of the study an improved method for high efficiency aerodynamic design of turbocompound systems was developed. Based on this method the parts of the TC system were aerodynamically optimized. The performance of the new design was verified by CFD. Improvements in the power output up to 10% were achieved in stationary engine points. Copyright © 2013 by ASME.
UnivIS-Import:2015-04-16:Pub.2013.tech.ITC.stmmec.cfdana